Unique hue data for colour appearance models. Part II: Chromatic adaptation transform. Issue 1 (1st October 2011) - Xiao, Kaida; Fu, Chenyang; Mylonas, Dimitris; Karatzas, Dimosthenis; Wuerger, Sophie
Abstract Unique hue settings of 185 observers under three room‐lighting conditions were used to evaluate the accuracy of full and mixed chromatic adaptation transform models of CIECAM02 in terms of unique hue reproduction. Perceptual hue shifts in CIECAM02 were evaluated for both models with no clear difference using the current Commission Internationale de l'Éclairage (CIE) recommendation for mixed chromatic adaptation ratio. Using our large dataset of unique hue data as a benchmark, an optimised parameter is proposed for chromatic adaptation under mixed illumination conditions that produces more accurate results in unique hue reproduction. © 2011 Wiley Periodicals, Inc. Col Res Appl, 2013